Emergy based sustainability evaluation of a hydroelectric dam proposal in South Asia. (10th August 2020) - Ali, Mustafa; Liu, Lingxuan; Geng, Yong; Khokhar, Shahid
Abstract: Pakistan is a resource-constrained country facing severe power shortages. To address the power demand-supply gap, Pakistan has increased its use of fossil fuel energy sources for power generation. To support a lower carbon power supply Pakistan needs renewable energy sources such as hydropower. However, most of the water for irrigation and power generation in the country is derived from a watershed in a disputed territory shared between India and Pakistan. Construction of hydroelectric dams over transboundary rivers have led to concerns regarding their ecological impacts. In this paper, we evaluated the sustainability of the Bursar Hydroelectric Project, proposed on such a transboundary river. Emergy analysis was used to holistically determine the change in the intrinsic value of the local ecosystem both before and after the construction of the dam. The results show that the project would increase the qualitative value of outputs derived from the local ecosystem. However, it would also extract and stock significant resources thus decreasing the overall sustainability of the system. In conclusion, the construction of the subject dam has negative consequences for unrestricted flow of water, sediments and biomass downstream. Policy makers can use this study to design mitigation measures for ecological conservation.